Rare Earth Frontiers From Terrestrial Subsoils to Lunar Landscapes - Klinger, Julie Michelle (Cornell University Press, 2018)
Owing to their unique magnetic, phosphorescent, and catalytic properties, rare earths are the elements that make possible teverything from the miniaturization of electronics, to the enabling of green energy and medical technologies, to supporting essential telecommunications and defense systems. An iPhone uses eight rare earths for everything from its colored screen, to its speakers, to the miniaturization of the phone's circuitry. On the periodic table rare earth elements comprise a set of seventeen chemical elements (the fifteen lanthanides plus scandium and yttrium). There would be no Pokémon Go without rare earths. Rare Earth Frontiers is a work of human geography. Klinger looks historically and geographically at the ways rare earth elements in three discrete but representative and contested sites are given meaning.